Poly(ophenylenediaminecoaniline)/ZnO coated on passivated low nickel stainless steel - Karthikeyan, P. (H. : ĐHQGHN, 2017)
Iron and its alloys are broadly used in many applications, which have strengthened the research in corrosion resistance in various neutral and provoking environments. Almost powerful corrosion in-hibitors have negative effects on both environment and health. Therefore, there is a need for a primer that provides outstanding adherence and corrosion resistance, and is environmentally safer. The con-ducting polymer coating on metals was found to offer the anti-corrosion. In this work, the Poly(o-phenylenediamine-co-aniline) copolymers (P(Popd-co-Ani)) and Poly(o-phenylenediamine-co-aniline)/ZnO (P(Popd-co-Ani)/ZnO) composite were synthesized using the electrochemical techniques on borate passivated low nickel stainless steel (LN SS) electrodes from lithium perchlorate in acetonitrile solutions containing afixed concentration of monomer and different concentrations of zinc oxide (ZnO). The structural and morphological analyses of the copolymer and composite coatings were conducted by Fourier transform-infrared spectroscopy (FT-IR), X-ray diffraction (XRD),field emission scanning electron microscopy (FE-SEM), elemental mapping and energy dispersion X-ray spectroscopy (EDX). The surface topography was assessed with using an atomic force microscope (AFM), and the corrosion protection behavior of these copolymer-coated stainless steels was investigated in a 0.5 M H2SO4solution by the potentiodynamic polarization (Tafel) and electrochemical impedance spectroscopy methods. Among the as developed protective copolymer coatings, the P(Popd-co-Ani)/ZnO composite exhibited the best corrosion protection